2014
DOI: 10.2535/ofaj.91.5
|View full text |Cite
|
Sign up to set email alerts
|

Human fetal topographical anatomy of the femoral triangle in relation with change in the hip joint position.

Abstract: Summary: Fetal hip joint is characterized by its highly flexion and lateral rotation although adult anatomy of the femoral nerve and iliofemoral ligament suggested the medial rotation. To investigate topographical anatomy of the femoral nerve, artery and vein in the femoral triangle, we histologically examined 11 fetuses (15-37 weeks). The nerve-vessel topographical relation was basically similar to that in adults, but the fan-like nerve division was seen in the horizontal plane in the smaller specimens in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The main issue of the research in this paper was the study of the intramuscular distribution of nerves and arteries and their interrelations in the medial group of the femoral muscles in human fetuses. When studying this issue, it was revealed that not all the muscles of the medial femoral group are equally intensively supplied with intramuscular nerves and arteries, and not all muscles have the same degree of individual anatomical variability 17 .…”
Section: Resultsmentioning
confidence: 99%
“…The main issue of the research in this paper was the study of the intramuscular distribution of nerves and arteries and their interrelations in the medial group of the femoral muscles in human fetuses. When studying this issue, it was revealed that not all the muscles of the medial femoral group are equally intensively supplied with intramuscular nerves and arteries, and not all muscles have the same degree of individual anatomical variability 17 .…”
Section: Resultsmentioning
confidence: 99%